Analysis Of The Impact Of Interest Rate Changes And Inflation On The Valuation Value Of Early Start-Ups In Indonesia - Leni Hartati; RR. Ella Evrita H (International Journal of Business and Quality Research, 2025)
This study aims to analyze the effect of the benchmark interest rate (BI Rate) and inflation on startup investment in Indonesia. Using secondary data for the period 2015–2025, a linear regression analysis was conducted to test the relationship between variables. The results showed that the BI Rate has a negative relationship with startup investment (regression coefficient -1.051; p = 0.337), but is not statistically significant. Conversely, inflation shows a positive relationship (regression coefficient 1.343; p = 0.276), but is also not significant. These findings indicate that macroeconomic factors such as interest rates and inflation have not become the main determinants in startup investment decisions. Other factors such as government policies, access to funding, and technological innovation are thought to have a more dominant influence.